A rapid novel strategy for screening of antibody phage libraries for production, purification, and functional characterization of amber stop codons containing single‐chain antibody fragments. (8th March 2021) - Perween, Reshma; Ahmed, Shubbir; Shrivastava, Tripti; Parray, Hilal A.; Singh, Balwant; Pindari, Kamal S.; Sharma, Chandresh; Shukla, Shivangi; Sinha, Subrata; Panchal, Anil Kumar; Kumar, Rajesh
Abstract: Phage display antibody (PDA) libraries, allows the rapid isolation and characterization of high specificity monoclonal antibodies for therapeutic and diagnostic applications. However, selection of positive binding clones from synthetic and semi‐synthetic libraries has an inherent bias towards clones containing randomly generated amber stop codons, complicating the identification of high affinity binding antibodies. We screened Tomlinson I and J library against receptor binding domain (RBD) of SARS CoV2, eight clones which showed positive binding in phage ELISA, contained one or more amber stop codons in their single‐chain antibody fragment (scFv) gene sequences. The presence of amber stop codons within the antibody sequence causes the premature termination of soluble form of scFv expression in nonsuppressor Escherichia coli strain. In the present study, we have used a novel strategy that allows soluble expression of scFvs having amber stop codon in their gene sequences (without phage PIII protein fusion), in the suppressor strain. This strategy of introduction of Ochre (TAA) codon at the junction of scFv and PIII gene, speeds up the initial screening process which is critical for selecting the right scFvs for further studies. Present strategy leads to the identification of a scFv, B8 that binds specifically with nanomolar affinity toward SARS CoV 2 RBD, which otherwise lost in terms of traditional methodology.